Relationship between Mindfulness and Cognitive Abilities in Blind Veteran Athletes - J. Rahmani; B. Ajilchi; E. Zareian (Afarand Scholarly Publishing Institute, 2017)
Aims: Cognitive abilities and mindfulness are factors hugely improving athletic activities. Blind persons, due to their lack of visual fast and accurate information, have to try to do cognitive executive tasks.  The aim of the study was to investigate the correlation between mindfulness and cognitive abilities in the athlete blind veterans. Instrument & Methods: In the correlative descriptive-survey study, 104 female and male athlete blind veterans from West Azarbayjan and Kordestan provinces were studied in 2015.  The subjects were selected via available sampling method. Data was collected by the mindfulness scale, attention and consciousness scale, and the cognitive abilities questionnaire. Data was analyzed by SPSS 22 software using Pearson correlation coefficient and linear regression analysis. Findings: Except in two components including inhibiting control and selective attention and planning, mindfulness positively and significantly correlated with cognitive abilities in other components (p<0.05). In addition, 0.438 of cognitive abilities variance in the blind persons were predicted by mindfulness (p=0.001). Conclusion: In the athlete blind veterans, mindfulness significantly correlates with some components of cognitive abilities including memory, decision-making, sustainable attention, social cognition, and cognitive flexibility. Therefore, regular mindfulness exercises can strengthen cognitive abilities in the blind veterans.